THE SIGNIFICANCE OF LIQUIDITY, PROFITABILITY, AND SOLVENCY RATIOS ON FINANCIAL STABILITY: A SYSTEMATIC LITERATURE REVIEW - M. Rizki Maulidi; Siti Nabila; Dhea Anggia; Adela Amanda; Miralda Salsabila Aisyah; Mariana Mariana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
This study aims to examine the effect of financial ratios—including liquidity, profitability, and solvency—on corporate financial stability using a systematic literature review (SLR) approach. Data were collected from various scholarly articles published between 2013 and 2023, selected based on topic relevance and publication quality. The analysis focuses on Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) as representative indicators of each financial ratio category. The findings reveal that these financial ratios play a crucial role in reflecting a company’s financial health and stability. ROA indicates asset management efficiency, CR reflects the company’s ability to meet short-term obligations, and DER reveals capital structure and financial risk. Therefore, these financial ratios serve as vital diagnostic tools for corporate financial assessment and decision-making.